(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
The purpose of this research is to evaluate the technological strategies applied by teachers in the teaching- learning process for the understanding of Social Sciences, particularly history. Being a descriptive study with a qualitative approach, with some quantitative implications. Where it is reflected in the study conducted by Peña and Pineda (2015) where they applied interviews and surveys to both teachers and students of the Social Sciences career of the UNAN-Managua, reflecting that the teachers of History of Nicaragua have very little knowledge of the Tics and therefore do not use the technological resources that the institution offers them to apply in the teaching-learning process, it was also detected that they only use the traditional methodology when applying the oral discourse and the exhibitions in the classroom. Where you must constantly train for the application of Tics in the teaching-learning process and motivate students to make use of technological resources to better understand the subject thus overcoming the weaknesses in this context.